Investigation of strategies to enhance the delivery of oncolytic vaccinia virus - Hill, C (2020)
Vaccinia Virus (VV) is an attractive vector for oncolytic virotherapy given its potential for tumour-selective tropism, efficient cell-to-cell spread, rapid replication in cancer cells, large transgene coding capacity and stimulation of anti-tumour immunity. It has a well-defined safety profile and is being assessed in latestage clinical trials.